DEMOCRATIC MANAGEMENT AND INNOVATION IN SCHOOL ADMINISTRATION: PATHWAYS TO PARTICIPATORY EDUCATION (REMUNOM, 2026)
Contemporary school administration requires a transition from centralized models to democratic governance ecosystems sustained by innovation. This study, designed as a theoretical essay based on an integrative literature review, analyzes how participatory management can be enhanced by data intelligence. The main objective is to investigate the effectiveness of Decision Engineering in designing administrative flows that promote transparency and real community inclusion. The methodology followed the six-stage protocol for integrative reviews, analyzing evidence collected between 2021 and 2026. The results demonstrate that the application of decentralized architectures (Data Mesh) and administrative MLOps practices allows for mitigating bureaucratic technical debt and strengthening school councils. It is concluded that the competitive advantage of educational institutions lies in the ability to transform participation into an ethical, stable, and technologically governed governance asset.